The Secret Book of Hermilio Valdizan: Reference peruvian documents to Carrion´s disease - Salinas-Flores , David (2023)
Hermilio Valdizán is considered the father of peruvian medical historiography, he had the desire to write an “Encyclopedia” of the peruvian wart. Recent medical journals reproduce Valdizán's complaint of not receiving government support in the publication of a reference book on Carrión's disease that gathers all the research on the Carrión's disease however, the book dreamed by Hermilio Valdizán was published. The book entitled “Peruvian documents referring to Carrión's disease” was edited by Hermilio Valdizán himself and Celso Bambaren, it brings together the biographies of the main wart researchers and its research from Salazar to the mid-20th century. Valdizán's “Encyclopedia” of the peruvian wart is practically unknown to most researchers of Carrión's disease, it should be considered as a milestone in the investigation of Carrión's disease, since it brings together the first investigations on the peruvian wart, it should be considered and known as the books “Carrión's disease” by Ernesto Odriozola or the “Peruvian Wart” by Raúl Rebagliati.